Feasibility and usability study of a pilot immersive virtual reality‐based empathy training for dental providers. Issue 6 (26th February 2021) - Amini, Homa; Gregory, Megan E.; Abrams, Mary Ann; Luna, John; Roland, Maxwell; Sova, Lindsey N.; Bean, Canise; Huang, Yungui; Pfeil, Sheryl A.; Townsend, Janice; Lin, En‐Ju D
Abstract: Purpose: Social determinants of health (SDOH) significantly impact individuals' engagement with the healthcare system. To address SDOH‐related oral health disparities, providers must be equipped with knowledge, skills, and attitudes (KSAs) to understand how SDOH affect patients and how to mitigate these effects. Traditional dental school curricula provide limited training on recognizing SDOH or developing empathy for those with SDOH‐related access barriers. This study describes the design and evaluation of such a virtual reality (VR)‐based simulation in dental training. We hypothesize the simulation will increase post‐training KSAs. Methods: We developed "MPATHI" (Making Professionals Able THrough Immersion), a scripted VR simulation where participants take the role of an English‐speaking caregiver with limited socioeconomic resources seeking dental care for a child in a Spanish‐speaking country. The simulation is a combination of 360 ° video recording and virtual scenes delivered via VR headsets. A pilot was conducted with 29 dental residents/faculty, utilizing a pre‐post design to evaluate effectiveness in improving immediate and retention of KSAs toward care delivery for families facing barriers. Results: MPATHI led to increased mean scores for cognitive (pre = 3.48 ± 0.80, post = 4.56 ± 0.51, p  < 0.001), affective (pre = 4.20 ± 0.4, post = 4.47 ± 0.44, p  < 0.001), and skill‐based learning (pre = 4.00 ± 0.47, post = 4.52 ± 0.37, p  < 0.001) immediately post‐training. There was not a significant difference between skills measured immediately post‐training and in the 1‐month post‐training survey ( p  = 0.41). Participants reported high satisfaction with the content and methods used in this training. Conclusions: This pilot study supports using VR SDOH training in dental education. VR technology provides new opportunities for innovative content design.